2016
DOI: 10.4081/reumatismo.2015.835
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory optic neuropathy in Behçet’s disease

Abstract: summary Inflammatory optic neuropathy (ON) is a rare event in Behçet's disease (BD). We report herein a series of ten BD Tunisian patients with ON and describe its clinical features among them. A retrospective review of BD patients (International Study Group for BD criteria) was performed. The patients were divided into two groups: those presenting an inflammatory ON, and those none. The diagnosis of inflammatory ON was based on the clinical examination, visual field and visual evoked potentials. We analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In relation to eye involvement in BD, most studies have described an optic neuropathy and retinal pathology with maculopathy and retinal neovascularization ( 19 , 20 ). Studies using optical coherence tomography (OCT) have demonstrated a significant reduction in the thickness of the retinal nerve fiber layer ( 21 ), ganglion cell and inner plexiform layers in patients with BD ( 22 ), while another study showed an initial increase in the nerve fiber layer in those with a short duration of disease, with thinning in those with a longer duration of disease ( 23 ), certainly indicating retinal nerve fiber pathology in patients with BD.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to eye involvement in BD, most studies have described an optic neuropathy and retinal pathology with maculopathy and retinal neovascularization ( 19 , 20 ). Studies using optical coherence tomography (OCT) have demonstrated a significant reduction in the thickness of the retinal nerve fiber layer ( 21 ), ganglion cell and inner plexiform layers in patients with BD ( 22 ), while another study showed an initial increase in the nerve fiber layer in those with a short duration of disease, with thinning in those with a longer duration of disease ( 23 ), certainly indicating retinal nerve fiber pathology in patients with BD.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent article from Tunisia described 10 cases with inflammatory ON among a single-center series of 440 patients with BD. 9 In that series, 50% of the cases had also various forms of other ocular involvement (retinal vasculitis in 1 and anterior/posterior/pan uveitis in 4). In the end, only 20% had vision loss, 40% had improvement, and 40% was stable.…”
Section: Discussionmentioning
confidence: 84%
“…4 Since then, optic neuropathy (ON) has rarely been reported in BD, probably as it was overshadowed by the more common ocular complication of BD, uveitis. 59 …”
mentioning
confidence: 99%
“…Three of 6 (50%) patients who underwent orbital magnetic resonance imaging (MRI) showed abnormal signals in the optic nerves. Khanfir et al 12 reported 10 patients with inflammatory optic neuropathy. No specific lesions of the optic nerve were noted on neuroradiological studies.…”
Section: Introductionmentioning
confidence: 99%